Clinical Features of Coexisting Anti-NMDAR and MOG Antibody-Associated Encephalitis: A Systematic Review and Meta-Analysis - Ding, Jiayue; Li, Xiangyu; Tian, Zhiyan (Frontiers in Neurology, 2021)
Coexisting anti-NMDAR and MOG antibody (anti-NMDAR-IgG+/MOG-IgG+)-associated encephalitis have garnered great attention. This study aimed to perform a secondary analysis to determine the clinical features of this disease. We searched several databases for related publications published prior to April 2021. A pooled analysis was conducted with the fixed-effects model using the Mante-Haenszel method (I2≤50%), or the random-effects model computed by the DerSimonian-Laird method (I2>50%). Stata software (version 15.0 SE) was used for the analyses. Nine observational studies and 16 case reports (58 cases with anti-NMDAR-IgG+/MOG-IgG+, 21.0 [8.5, 29.0] years, male 58.6%) were included. The incidences (95%CI) of anti-NMDAR-IgG+/MOG-IgG+ in the patients with serum MOG-IgG+ and CSF anti-NMDAR-IgG+ were 0.09(0.02-0.19) and 0.07(0.01-0.19) respectively. The median[IQR] of CSF anti-NMDAR antibody titer was 32[10, 100], and the serum anti-MOG antibody titer was 100[32, 320]. The prominent clinical symptoms were encephalitic manifestations, including seizures (56.9%) and abnormal behavior (51.7%), rather than demyelinating manifestations, such as speech disorder (34.5%) and optic neuritis (27.6%). Relapse occurred in 63.4% of anti-NMDAR-IgG+/MOG-IgG+ patients, in whom 50.0% of cases relapsed with encephalitic manifestations, and 53.8% relapsed with demyelinating manifestations. The common MRI changes were in the cortex or subcortex (70.7%) and brainstem (31.0%). 31.3% of patients presented with unilateral cerebral cortical encephalitis with epilepsy and 12.5% displayed bilateral frontal cerebral cortex encephalitis. Anti-NMDAR-IgG+/MOG-IgG+ patients showed more frequent mental behavior (OR, 95%CI, 68.38, 1.36-3434.37), involuntary movement (57.86, 2.53-1325.11), sleep disorders (195.00, 7.07-5380.15), and leptomeninge lesions (7.32, 1.81-29.58), and less frequent optic neuritis (0.27, 0.09-0.83) compared to anti-NMDAR-IgG-/MOG-IgG+ patients and presented more common relapse (5.63, 1.75-18.09), preceding infection (2.69, 1.03-7.02), subcortical lesions (116.60, 4.89-2782.09), basal ganglia lesions (68.14, 2.99-1554.27), brainstem lesions (24.09, 1.01-574.81), and spinal cord lesions (24.09, 1.01-574.81) compared to anti-NMDAR-IgG+/MOG-IgG-. In conclusion, anti-NMDAR-IgG+/MOG-IgG+ was rarely observed, but the incidence rate of relapse was very high. The overall symptoms seemed to be similar to those of NMDAR encephalitis.